Adventures of Johnny Vermillion - Estleman, Loren D. (New York Forge, 2008)
Heading up a theater troupe that journeys throughout the wild western frontier, Johnny Vermillion uses their performances as a clever cover-up for a bank robbery operation that is being investigated by a suspicious Pinkerton man.
Reprint. Originally published: 2006.
"A Tom Doherty Associates book."
93105
Keywords: Bank robberies; Theatrical companies